von Hippel-Lindau Syndrome: Genetic Study of Case With a Rare Pathogenic Variant With Optic Nerve Hemangioblastoma, a Rare Phenotypic Expression - Boratto, Sandra Di Felice; Cardoso, Pedro Augusto Soffner; Priolli, Denise Gonçalves; Botelho, Ricardo Vieira; Goldenberg, Alberto; Bianco, Bianca; Waisberg, Jaques (Frontiers in Oncology, 2020)
von Hippel-Lindau syndrome (VHLS) is a rare, autosomal dominant genetic disease with high penetrance and variable phenotypic expression caused by vaiants in the VHL gene. VHLS is associated with the presence of vascular tumors, often hemangioblastoma of the central nervous system, retina, or spinal cord and, less frequently, pancreatic cystic neoplasm, pancreatic neuroendocrine tumor, clear cell carcinoma of the kidney, endolymphatic sac tumor, pheochromocytoma, and paraganglioma. The authors report a case of a patient with VHLS with a rare pathogenic variant in the VHL gene and with an optic nerve hemangioblastoma, a rare phenotypic expression. Case report: A 49-year-old woman was diagnosed with cystic neoplasm of the pancreas, renal cell carcinoma of the right kidney, and hemangioblastoma of the left optic nerve. The patient’s family history revealed siblings with VHLS manifestations. The index case was her mother who died at age 63 of clear cell renal carcinoma. The information was obtained by consulting the patient’s medical register and by interviews with the patient and her relatives. The presence of left optic nerve hemangioblastoma was suggested by CT scan of the skull and orbit. The sequencing of the VHL gene was performed in the peripheral blood by the polymerase chain reaction (PCR) technique, and the duplication and deletion research was performed using the multiplex ligation-dependent probe amplification (MPLA) technique. The presence of a rare pathogenic variant c.263G> A (p.Trp88Ter) was observed in heterozygosity in the VHL gene that determined a premature stop codon. CT scan of the skull and orbits suggested the presence of HB in the optic nerve of the left eye. The results of the CT scan of the skull and orbits show thickening with tortuosity of the left optic nerve, with a small area of nodular enhancement. The right optic nerve had a conserved aspect. Conclusion: This is the fourth case described of this rare pathogenic variant of the VHL gene, according to the Human Gene Mutation Database and VHLdb database records and with an optic nerve hemangioblastoma of the optic nerve, a very rare phenotypic expression of the VHLS.